DEAD-box protein Ddx46 is required for the development of the digestive organs and brain in zebrafish. - Shunya Hozumi; Ryo Hirabayashi; Akio Yoshizawa; Mitsuko Ogata; Tohru Ishitani; Makiko Tsutsumi; Atsushi Kuroiwa; Motoyuki Itoh; Yutaka Kikuchi (PLoS ONE)
Spatially and temporally controlled gene expression, including transcription, several mRNA processing steps, and the export of mature mRNA to the cytoplasm, is essential for developmental processes. It is well known that RNA helicases of the DExD/H-box protein family are involved in these gene expression processes, including transcription, pre-mRNA splicing, and rRNA biogenesis. Although one DExD/H-box protein, Prp5, a homologue of vertebrate Ddx46, has been shown to play important roles in pre-mRNA splicing in yeast, the in vivo function of Ddx46 remains to be fully elucidated in metazoans. In this study, we isolated zebrafish morendo (mor), a mutant that shows developmental defects in the digestive organs and brain, and found that it encodes Ddx46. The Ddx46 transcript is maternally supplied, and as development proceeds in zebrafish larvae, its ubiquitous expression gradually becomes restricted to those organs. The results of whole-mount in situ hybridization showed that the expression of various molecular markers in these organs is considerably reduced in the Ddx46 mutant. Furthermore, splicing status analysis with RT-PCR revealed unspliced forms of mRNAs in the digestive organ and brain tissues of the Ddx46 mutant, suggesting that Ddx46 may be required for pre-mRNA splicing during zebrafish development. Therefore, our results suggest a model in which zebrafish Ddx46 is required for the development of the digestive organs and brain, possibly through the control of pre-mRNA splicing.